May magic si inay! Mommy knows magic! - Matias, Segundo D.; Agarao, Rowen; Bravo, Becky; Garcia, Edith (Maynila Lampara Publishing House, Inc., 2009)
"Find out in this story what the best medicine is for children's ailments, and who alone in the world can provide it."
"Stories with moral values."
Text in English and Filipino.
Keywords: Children's stories, Philippine (English)